2013
DOI: 10.1177/039463201302600424
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Administration of Hyaluronan as a Further Resource in Olfactory Performance in Multiple Chemical Sensitivity Syndrome

Abstract: Multiple chemical sensitivity (MCS) is a relatively common clinical diagnosis in western populations and its symptoms (i.e. dysosmia) are mainly triggered by chemical compounds, such as common odorants. The aim of this study was to test the effect of intranasal administration of hyaluronic acid (HA) on odour threshold and related quality of life in MCS syndrome. Two randomized groups of MCS patients received 30 days’ administration of either a nasal spray (Ialumar®) containing HA [HA group (HAG); n=29] or only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 19 publications
2
22
0
2
Order By: Relevance
“…Before undergoing to olfactory stimulation all subjects completed the following VQ:Questionnaire of Olfactory Disorders (QOD) - completed only before NC phase - to assess daily life problems due to olfactory impairment, we used a short modified version of an olfactory-specific QOD developed by Frasnelli and Hummel40 which has recently been used by many researchers41. The modified short version of the QOD consists of 25 statements that are divided into three general domains: 17 negative statements (QOD-NS), two positive statements (QOD-PS), and six socially desired statements (QOD-SD);…”
Section: Methodsmentioning
confidence: 99%
“…Before undergoing to olfactory stimulation all subjects completed the following VQ:Questionnaire of Olfactory Disorders (QOD) - completed only before NC phase - to assess daily life problems due to olfactory impairment, we used a short modified version of an olfactory-specific QOD developed by Frasnelli and Hummel40 which has recently been used by many researchers41. The modified short version of the QOD consists of 25 statements that are divided into three general domains: 17 negative statements (QOD-NS), two positive statements (QOD-PS), and six socially desired statements (QOD-SD);…”
Section: Methodsmentioning
confidence: 99%
“…Multiple chemical sensitivity (MCS) is a chronic polysymptomatic, multisystem condition characterized by subjective susceptibility to low levels of a wide spectrum of environmental compounds (such as petrol, perfume or pesticides) [1,2]. It constitutes a relatively common clinical diagnosis in western populations [2], considering that the prevalence of self-reported chemical sensitivity symptoms in population-based studies has been found to range from 9% to 33% [2].…”
Section: Introductionmentioning
confidence: 99%
“…It constitutes a relatively common clinical diagnosis in western populations [2], considering that the prevalence of self-reported chemical sensitivity symptoms in population-based studies has been found to range from 9% to 33% [2]. Relapsing and remitting central nervous system (CNS) manifestations including difficulty concentrating, memory problems, fatigue, depression, daytime sleepiness, "spaciness" (derealisation), tension, irritability and dizziness are commonly referred to by the patients [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations